Linking field and farmer surveys to determine the most important changes to weed incidence - Borger, C.; Michael, Pippa; Mandel, R.; Hashem, A.; Bowran, D.; Renton, M. (Blackwell Scientific Publications, 2012)
An understanding of weed species incidence and patterns of change in incidence is vital in developing weed management strategies and directing future research endeavours. Weed incidence in fields in the south-west of Western Australia was surveyed in 1997 and repeated in 2008 to determine any changes. In 2008, farmers were also surveyed to determine their perception of changes to weed incidence and severity. The field survey identified a total of 194 weed species (or groups of a genus) in the combined survey data set (i.e. 956 sites from both field surveys). The majority of survey sites were utilised for cropping, and 152 weed species were identified within cropped fields. Between 1997 and 2008, noticeable decreases in incidence (in cropped fields) were observed for Vulpia spp. (-25%), Aira caryophyllea (-21%), Bromus diandrus (-20%), Avena fatua (-18%) and Austrostipa spp. (-13%), with only Raphanus raphanistrum (11%) and Arctotheca calendula (7%) significantly increasing in frequency. Farmer perception of the most severe weed problems did not always coincide with survey results of weed incidence. For example, an exceptionally common weed like A. calendula (with increasing incidence) was of less concern to farmers than the extremely rare Conyza spp. The main conclusion of this research is that the prevalence of a weed species is not always an indication of whether the species is of economic concern to industry. Therefore, it is vital to link field survey results to industry perception of weed species severity, when directing future research efforts into weed management.